(untitled) (Jurnal Manajemen dan Organisasi, 2020)
The function of organizational culture is to engage all components of the organization, determining identity, energy injections, motivators, and can be used as guidelines for members of the organization. Organizational Culture is one of the key successes of BPPI in the assessment of PMPRB. The purpose of this research is to answer: (1) How the realization and expected of organizational culture at BPPI Ministry of Industry? (2) How is the leadership style of BPPI leadership of the Ministry of Industry that is analyzed through the perception of leaders and employees by Using Management Skill Assessment Instrument (MSAI)? (3) How recommendations are given regarding managerial implications of organizational culture and leadership style that need to be improved Upgrade to BPPI. The Research results of the organization BPPI Ministry of Industry realization is more likely to dominate to Clan culture and hierarchy. While the expected culture of BPPI Ministry of Industry to be more likely to dominate to Clan culture and Adhocracy.